2005
DOI: 10.1016/j.ccr.2005.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional repressor Snail promotes mammary tumor recurrence

Abstract: Breast cancer recurrence is a fundamental clinical manifestation of tumor progression and represents the principal cause of death from this disease. Using a conditional transgenic mouse model for the recurrence of HER2/neu-induced mammary tumors, we demonstrate that the transcriptional repressor Snail is spontaneously upregulated in recurrent tumors in vivo and that recurrence is accompanied by epithelial-to-mesenchymal transition (EMT). Consistent with a causal role for Snail in these processes, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
555
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(597 citation statements)
references
References 40 publications
32
555
3
4
Order By: Relevance
“…In these models, recurrent tumors displaying features of EMT were found to contain increased mRNA levels of the E-cadherin transcriptional repressors Snail (Moody et al, 2005;Debies et al, 2008) and to a lesser degree Slug (Moody et al, 2005). In addition, Snail itself was shown to play a causal role in promoting recurrence of fully regressed erbB2-induced tumors (Moody et al, 2005). In agreement with these studies, we also found that Snail and Slug mRNA levels were upregulated in our EMT tumors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In these models, recurrent tumors displaying features of EMT were found to contain increased mRNA levels of the E-cadherin transcriptional repressors Snail (Moody et al, 2005;Debies et al, 2008) and to a lesser degree Slug (Moody et al, 2005). In addition, Snail itself was shown to play a causal role in promoting recurrence of fully regressed erbB2-induced tumors (Moody et al, 2005). In agreement with these studies, we also found that Snail and Slug mRNA levels were upregulated in our EMT tumors.…”
Section: Discussionsupporting
confidence: 89%
“…Mammary tumor escape from the initiating oncogene, accompanied by EMT, has been reported in similar doxycycline inducible breast cancer models. In these models, recurrent tumors displaying features of EMT were found to contain increased mRNA levels of the E-cadherin transcriptional repressors Snail (Moody et al, 2005;Debies et al, 2008) and to a lesser degree Slug (Moody et al, 2005). In addition, Snail itself was shown to play a causal role in promoting recurrence of fully regressed erbB2-induced tumors (Moody et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As TWIST is not significantly differentially expressed in the fibroblastic cell lines, we suggest that its protein product has a direct effect on CDH1 and results in a similar phenotype as CDH1 mutations, thereby contributing to the typical phenotype of lobular breast cancer. The lack of upregulation of SNAI1 is unexpected, especially given the recently identified role of this gene in breast cancer recurrence (Moody et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors that are induced in the MMTV-rtTA/TetO-NeuNT model and which completely regress upon oncogene withdrawal, eventually recur after prolonged dormancy without induction of the neuT oncogene (Moody et al, 2002). This is associated with induction of the transcriptional repressor snail, and suggests that second hits may provide escape routes for residual tumor cells leading to tumor recurrence and progression driven by alternative pathways (Moody et al, 2005). Tetracycline-regulated NIH3T3-HER2 tumors cells that regress following withdrawal of oncogene expression similarly recur following a period of remission despite absence of oncogene expression, although the molecular features associated with HER2-independent recurrence in this model are not yet described (Schiffer et al, 2003).…”
Section: Potential To Escape From Her2 Addictionmentioning
confidence: 99%